Guest Editorial Advances in Energy Conversion, Control, Operation and Planning Towards Self-Sustained Highway Transportation Energy System - Ding, Zhaohao; Dehghanian, Payman; He, Jiangbiao; Fang, Sidun; Illindala, Mahesh; Sarikprueck, Piampoom; Bidram, Ali (My University, 2024)
As a major components of modern transportation systems, the highway transportation system is one of the most significant carbon emission contributors in the entire transportation sector. Although there are numerous distributed renewable resources along the highway system, their diversified inherent characteristics and heterogeneous operational conditions present challenges to fully utilize those clean energy resources for the highway transportation system. Towards the carbon neutrality targets, it is important to investigate the integrated multi-energy conversion, control, operation and planning for the self-sustained highway transportation system from an energy-transportation nexus perspective. Therefore, the coordinated interaction of the various components of the highway transportation energy system becomes essential. This entails not only advancements in energy conversion technologies but also the development of intelligent control systems, sustainable operational models, and forward-thinking planning to enable self-sustained energy ecosystems along the highway.